ARTIFICIAL INTELLIGENCE IN TANZANIA'S HIGHER EDUCATIONAL INSTITUTIONS: A PHILOSOPHICAL REFLECTION ON ETHICS AND HUMAN INTELLIGENCE: ST. AUGUSTINE UNIVERSITY OF TANZANIA AND THE MWALIMU NYERERE MEMORIAL ACADEMY AS CASE STUDIES - Theophil, Christopher; Innocent , Sanga; Matiko, Charles, Adam (Journal of E-Learning and Educational Technologies (JEET), 2024)
This Paper delves into the ethical implications of integrating artificial intelligence [AI] technologies in Tanzanian higher education institutions, focusing on St. Augustine University of Tanzania [SAUT] and The Mwalimu Nyerere Memorial Academy [MNMA]. This study examines the influence of sex, age, and education on AI integration; the impact of AI on learning processes and assessment outcomes, the significance of AI in preparing graduates for the workforce, and the effectiveness of AI in personalizing learning experiences for students. Through descriptive and cross-sectional designs, data were obtained from academic staff and students from SAUT and MNMA, with findings highlighting gender disparity, diverse age distribution, and positive perceptions toward AI in education. Interviewed Participants highlighted the benefits of AI while expressing concerns about potential challenges such as teacher substitution, student behavior, creativity limitations, and data privacy issues. This Paper underscores the importance of engaging with diverse perspectives in addressing ethical considerations for the responsible integration of AI in Tanzanian universities